Drying effect by infrared radiation on sensory quality in special coffees (Coffea arabica) cup - Guevara-Sánchez, Maricely; Guevara-Sánchez, Karen; Quispe-Cubas, Neiser; Valles-Coral, Miguel; Navarro-Cabrera, Jorge; Pinedo, Lloy (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The drying process of coffee (Coffea arabica) is important to achieve quality organoleptic characteristics. The objective of the study was to evaluate the effect of drying by means of an electromechanical system based on infrared on sensory quality in special coffees cup. For this, an electromechanical system was designed using infrared emitters that combines electromagnetic radiation with conventional convective heating. 75 coffee samples were collected at three (3) height levels. The samples underwent the traditional drying process and the electromechanical system, to later be evaluated by professional tasters under the SCAA (Specialty Coffee Association of America) scale. The samples dried with infrared at 12% humidity presented a cupping value of 82.93 for cup coffee with a smaller data dispersion than the traditional system that obtained 81.34, in addition the t-test of non-equivalent samples indicates that its value is significantly better (p<0.05). We concluded that the electromechanical system with infrared drying increased the sensory quality of coffee compared to traditional drying.